2003
DOI: 10.1046/j.1365-2362.2003.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise induces excessive normetanephrine responses in hypertensive diabetic patients

Abstract: The excessive response of plasma unconjugated normetanephrine to cycling may serve as a marker of exaggerated sympathoadrenal function in hypertensive type-2 diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…, 16 cycling exercise led to significantly elevated plasma normetanephrine. Similarly, Raber showed significant increases in normetanephrine during cycling exercise, but almost negligible raises in metanephrine 22 . These findings were confirmed by Bracken et al.…”
Section: Discussionsupporting
confidence: 61%
“…, 16 cycling exercise led to significantly elevated plasma normetanephrine. Similarly, Raber showed significant increases in normetanephrine during cycling exercise, but almost negligible raises in metanephrine 22 . These findings were confirmed by Bracken et al.…”
Section: Discussionsupporting
confidence: 61%
“…Plasma metanephrines are stable markers of catecholamine secretion and have previously been reported to reflect physiological stress and the sympathoadrenal response to cycling exercise (Raber et al 2003). The fact that PNORMET increased under all experimental conditions with exercise suggests that the protocol was sufficiently provocative to induce the required physiological stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the physiologic cause for the observed relationship of normetanephrine measurements with age is unclear. Of note, Raber et al have noted exaggerated increases in plasma normetanephrine after exercise in hypertensive individuals with type 2 diabetes, compared to normotensive individuals with or without diabetes [20]. Furthermore, Raber et al have suggested that the excessive response of plasma normetanephrine to exercise may serve as a marker of exaggerated sympathoadrenal function in hypertensive type 2 diabetics [20].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, Raber et al have noted exaggerated increases in plasma normetanephrine after exercise in hypertensive individuals with type 2 diabetes, compared to normotensive individuals with or without diabetes [20]. Furthermore, Raber et al have suggested that the excessive response of plasma normetanephrine to exercise may serve as a marker of exaggerated sympathoadrenal function in hypertensive type 2 diabetics [20]. Fractionated plasma metanephrine measurements were performed only at rest in our study and we did not examine any potential relationship with diabetes.…”
Section: Discussionmentioning
confidence: 99%